Arrays of needle-like TiO2/CdS nanorod heterostructure photoelectrodes with enhanced photoelectrochemical properties fabricate by pulsed laser deposition. (February 2021) - Lu, Yongjuan; Yi, Gewen; Zhou, Hancheng; Liu, Juanli; Zhang, Hong; Lu, Lina; An, Lili
Abstract: To improve the photoelectrochemical properties of TiO2 /CdS composite nanorod electrodes, we developed a one-step quantum dot (QD) synthesis and assembly process based on pulsed laser deposition (PLD). An advantage of this method is that it does not involve ligand-exchange processing or wet chemical methods that might destabilize the QD attachment. By using PLD, CdS QDs were successfully grown on a dense array of TiO2 nanorods, forming needle-like heterostructures whose photophysics depends on the laser pulse energy. The XRD results indicated that the products were composed of the tetragonal rutile, TiO2 and hexagonal CdS. The TiO2 /CdS heterostructures fabricated with this method are very stable and exhibit promising photoelectrochemical characteristics for photovoltaic applications. The best results are obtained for a PLD laser pulse energy of 300 mJ, which produces TiO2 /CdS heterostructure nanorod electrodes that, when illuminated at AM 1.5 G, have a photocurrent density exceeding 4.7 mA cm −2  at 0 V versus a saturated calomel electrode. Highlights: Pulsed laser deposition (PLD) is a promising technique for fabricating quantum dot (QD) without ligand-exchange. We grow CdS QDs on a dense array of TiO2 nanorods, forming needle-like heterostructures. TiO2 /CdS( N ) electrodes exhibit a stable photocurrent when illuminated with 100 mW cm −2 of simulated sunlight.